Recurrence and Satisfaction in Patients after Pterygium Surgery in Tertiary Eye Hospital in Bhaktapur, Nepal - Sharma, Samata; Khadka, Deepak; Shrestha, Arjun; Shrestha, Nirsara; Suwal, Barsha; Khatri, Bijay (Nepalese Journal of Ophthalmology, 2024)
Introduction: Pterygium is a common and benign condition that warrants surgical removal for ocular and cosmetic reasons. Pterygium excision with conjunctival autograft is frequently performed surgery in Nepal. Objective: This study is aimed to find out the recurrence and satisfaction following surgery. Methodology: This was a descriptive cross-sectional study conducted from August to October 2021 at a tertiary hospital in Bhaktapur. All the patients who had undergone pterygium surgery with conjunctival autograft surgery for primary pterygium from January 2018 to December 2019 and completed at least 6 months of follow-up were included. We reviewed records for surgery, complications, and recurrence from Medical Records. We also interviewed patients by phone for satisfaction related to symptomatic and cosmetic relief. The descriptive statistics were reported as frequency, mean, and standard deviation. The satisfaction score was measured on a 5-point Likert scale. Result: Among 142 patients, the mean age was 46.70±11.25 years, and 28.17% were males. 7.74% had complications and graft edema was the most common. The recurrence rate after surgery was 5.63%. The recurrence was higher among males and under 40 years patients. More than one-third of the patients reported they had surgery for symptomatic relief. The study showed high satisfaction scores for both symptomatic relief and cosmetic appearance, with scores of 3.62±0.93 and 3.87±0.96, respectively, on a 5-point Likert scale. Conclusion: Pterygium surgery with conjunctival autograft is safe surgery with minimal complications. Along with symptomatic relief, cosmetic satisfaction can be considered a measure of successful surgical outcome in pterygium surgery.